Reviving the Archives. The Researcher as Artist and the Artist as Researcher - MODREANU, Cristina (Studia Universitatis Babeș-Bolyai Dramatica, 2021)
How to make the archives live again for a contemporary audience? Based on the writings of a famous historian, Arlette Farge, and on my own experience in working with archives I am arguing in this article that the archive researcher should take inspiration from artistic creativity and artists should pay more attention to the scholar dimension of their research, while both need to understand they are accountable to the next generations for which they need to re-write the historical narrative in a responsible way, as close to the truth as possible.